Durability and Mechanical Performance of Ceramic Waste Powder and Activated Zeolite Blended Concrete under Sulfate and Chloride Attack (Indonesian Journal of Civil Engineering Study, 2026)
This study examines the mechanical and durability properties of concrete incorporating a binary supplementary cementitious material (SCM) comprising ceramic waste powder (CWP) and activated zeolite (AZ) in a 1:1 ratio. Six concrete mixes with cement replacement levels of 0%, 10%, 15%, 20%, 25%, and 30% were assessed under exposure to 5% Na₂SO₄ and 3.5% NaCl. Durability testing involved wet-dry cycling for 28, 56, and 90 days. The results indicate that the mix with 20% CWP-AZ (M3) exhibited optimal performance, retaining over 92% of its strength, achieving the lowest sorptivity (0.221 mm/√s), and demonstrating a significant reduction in mass loss (2.1%) ANOVA (F = 14.72, p < 0.001) and regression modeling confirmed significant durability gains. The findings offer a sustainable solution for concrete used in offshore and oilfield infrastructures.